Osteopontin promoter polymorphisms and risk of urolithiasis: a candidate gene association and meta-analysis study - Ali Amar; Ayesha Afzal; Athar Hameed; Mumtaz Ahmad; Abdul Rafay Khan; Humaira Najma; Aiysha Abid; Shagufta Khaliq (BMC, 2020)
Abstract Background Urolithiasis is a worldwide urological problem with significant contribution of genetic factors. Pakistan, which resides within the Afro-Asian stone belt, has a high reported prevalence (12%) of urolithiasis. Osteopontin (SPP1) is a urinary macromolecule with a suggested critical role in modulating renal stone formation, genetic polymorphisms of which may determine individual risk of developing urolithiasis. However, results of previous studies regarding SPP1 polymorphisms and susceptibility to urolithiasis have apparent inconsistencies with no data available for local population. Methods A total of 235 urolithiasis patients and 243 healthy controls, all of Pakistani ancestry, underwent genotyping for six SPP1 genetic polymorphisms in an effort to investigate potential association with urolithiasis using indigenous candidate gene association study design. Further, a comprehensive meta-analysis following a systematic literature search was also done to ascertain an evidence based account of any existent association regarding SPP1 promoter polymorphisms and risk of developing urolithiasis. Results Three SPP1 promoter polymorphisms, rs2853744:G > T, rs11730582:T > C and rs11439060:delG>G, were found to be significantly associated with risk of urolithiasis in indigenous genetic association study (OR = 3.14; p = 0.006, OR = 1.78; p = 0.006 and OR = 1.60; p = 0.012, respectively). We also observed a 1.68-fold positive association of a tri-allelic haplotype of these SPP1 promoter polymorphisms (G-C-dG) with risk of urolithiasis (OR = 1.68; p = 0.0079). However, no association was evident when data were stratified according to gender, age at first presentation, stone recurrence, stone multiplicity, parental consanguinity and family history of urolithiasis. The overall results from meta-analysis, which included 4 studies, suggested a significant association of SPP1 rs2853744:G > T polymorphism with susceptibility of urolithiasis (OR = 1.37; p = 0.004), but not for other SPP1 polymorphic variants analyzed. Conclusions In conclusion, we report significant association of 3 SPP1 polymorphisms with urolithiasis for the first time from South Asia, however, this association persisted only for SPP1 rs2853744:G > T polymorphism after meta-analysis of pooled studies. Further studies with a larger sample size will be required to validate this association and assess any potential usefulness in diagnosis and prognosis of renal stone disease.